Preparation method of high-purity molybdenum alloy composite material and application of high-purity molybdenum alloy composite material in metal fireplace

By modifying high-purity molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder and multi-pass processing, the problem of uneven alloy distribution in high-purity molybdenum alloy composite materials is solved, and the performance of the material is significantly improved.

CN119571115APending Publication Date: 2025-03-07YANGZHOU HUARUI METAL PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411786948.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Among the high-purity molybdenum alloy composite materials used in metal fireplaces, the alloy distribution inside the prepared material is uneven, affecting its mechanical properties, electrical and thermal conductivity and corrosion resistance.

Method used

High-purity molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder are used for modification treatment, and mixed through a V-shaped mixer, followed by compression, directional local melting, sintering, drawing, piercing and annealing treatment to form a high-purity molybdenum alloy composite material.

Benefits of technology

Through modification processing and multi-pass processing, the density and uniformity of the material are improved, the unevenness in the alloy is reduced, and the mechanical properties, electrical and thermal conductivity and corrosion resistance of the material are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571115A_ABST
    Figure CN119571115A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-purity molybdenum alloy composite material and application of the high-purity molybdenum alloy composite material in a metal fireplace, and the preparation method comprises the following steps: selecting high-purity molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder as raw materials, carrying out modification treatment on each powder, mixing the powder after modification treatment, pressing the mixed alloy powder, and sintering to obtain the high-purity molybdenum alloy composite material. The preparation method comprises the following steps of: forming a pressed blank, carrying out directional local melting on the pressed blank, sintering the pressed blank subjected to directional local melting, fully melting and combining, then carrying out multi-pass drawing and upsetting treatment, carrying out annealing treatment, and cooling to room temperature along with a furnace after annealing, so as to obtain a final material. A layer of uniform and compact protective film is formed on the surface of the alloy, so that the compactness and uniformity of the material are improved, the interaction between the material and subsequent treatment liquid is regulated and controlled, and the surface roughness is increased; the situation that the alloy of the integrally prepared high-purity molybdenum alloy composite material is not uniform is reduced, and the overall performance of the high-purity molybdenum alloy composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a molybdenum alloy composite material, and in particular to a method for preparing a high-purity molybdenum alloy composite material and application of the high-purity molybdenum alloy composite material in a metal fireplace. Background Art

[0002] In the field of materials science, the preparation of high-purity alloys has always been a hot topic and a difficult point of research. Molybdenum alloys have broad application prospects in aerospace, nuclear industry, electronics industry, high-temperature furnaces and other fields due to their excellent high temperature resistance, high strength, good electrical and thermal conductivity, and excellent corrosion resistance. At present, the methods for preparing high-purity molybdenum alloy composites mainly include powder metallurgy, smelting casting, and sputtering deposition.

[0003] The powder metallurgy method is to mix, press, sinter and other steps of high-purity metal powder to finally prepare the required alloy material. This method has the advantages of simple preparation process, easy control of composition, and ability to prepare parts with complex shapes. The smelting and casting method is to melt various metal raw materials into alloy liquid at high temperature, and then cast them into shape. The alloy material prepared by this method has uniform structure, but the composition control is relatively difficult, and there are great challenges in the preparation of high-purity alloys. The sputtering deposition method is to use high-energy particles to bombard the target material, so that the atoms or molecules on the surface of the target material are sputtered out and deposited on the substrate to form a thin film or coating. The alloy material prepared by this method has high purity and fine structure, but the preparation cost is high, and it is difficult to prepare large pieces of alloy material.

[0004] However, in the high-purity molybdenum alloy composite materials generally used in metal fireplaces, the alloy distribution inside the prepared high-purity molybdenum alloy composite materials is uneven, which will affect the mechanical properties, electrical and thermal conductivity, and corrosion resistance of the alloy material. Summary of the invention

[0005] The invention overcomes the shortcomings of the prior art and provides a preparation method of a high-purity molybdenum alloy composite material and application of the same in a metal fireplace.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a high-purity molybdenum alloy composite material and its application in a metal fireplace, comprising: S1, selecting high-purity molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder and performing modification treatments respectively;

[0007] S2, placing the modified molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder in a V-type mixer according to the weight ratio and mixing them, and adding a dispersant during the mixing process;

[0008] S3, placing the mixed alloy powder into a pressing mold, using a hydraulic press to press, the pressing pressure is 200MPa, the holding time is 5min, to obtain a compact;

[0009] S4, performing directional local melting on the compact;

[0010] S5. Place the compact after partial melting into a sintering furnace and pre-sinter it under vacuum conditions. The vacuum degree is controlled at 10 -3 Pa, heating rate is 5℃ / min, heating to 1600℃, keeping temperature for 2h;

[0011] S6. Formal sintering: Introduce protective gas into the sintering furnace, continue to heat up to 2000℃, and sinter for 8 hours. The temperature and atmosphere should be strictly controlled during the sintering process to ensure that the alloy powder is fully melted and combined. After sintering, cool to room temperature with the furnace to obtain a molybdenum alloy billet.

[0012] S7. The sintered molybdenum alloy billet is subjected to multiple drawing and roughening processes.

[0013] S8, annealing the roughened molybdenum alloy billet under vacuum conditions at a temperature of 1200° C. for 2 hours, and cooling the billet to room temperature to obtain a final material.

[0014] In a preferred embodiment of the present invention, in step S1, the specific steps of the modification treatment are as follows:

[0015] S11, washing the powder with ethanol to remove surface impurities, and placing the washed powder in a drying oven to remove moisture;

[0016] S12, using a combination of three modification methods: surface chemical coating modification method, precipitation reaction modification method and mechanochemical modification method;

[0017] S13, after the modification treatment, the powder is washed to remove unreacted modifier and impurities;

[0018] After washing, the powder is dried in a drying oven to remove moisture;

[0019] In a preferred embodiment of the present invention, in step S12, specifically including:

[0020] S121. Place molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder in different containers respectively; add an appropriate amount of silane coupling agent solution (KH-550) to each container to ensure that the solution can completely cover the powder; at 60°C, make the silane coupling agent uniformly adsorbed on the surface of the powder by stirring or ultrasound; after 2-4 hours, take out the powder, wash it with ethanol or other solvents to remove the unreacted silane coupling agent; place the washed powder in an oven to dry to obtain a modified powder;

[0021] S122, uniformly mixing the molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder modified in step S121; adding sodium hydroxide solution to the mixed powder to ensure that the concentration and pH value of the solution are appropriate; stirring at 60° C. to allow sodium hydroxide to react with metal ions on the surface of the powder to generate hydroxide precipitates; after the reaction is completed, filtering and washing the precipitates to remove unreacted sodium hydroxide and impurities; drying the washed precipitates in an oven to obtain modified powders;

[0022] S123, uniformly mixing the molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder modified in step S122; placing the mixed powder in an ultrafine grinding device to activate the particle surface through strong mechanical force; during the grinding process, adding stearic acid to react or adsorb the modifier to the powder surface through mechanical force; after the grinding and modification are completed, taking out the powder, screening and drying it to obtain the final modified powder.

[0023] In a preferred embodiment of the present invention, the weight ratio of the molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder is 65:7:7:8:13.

[0024] In a preferred embodiment of the present invention, the dispersant is silicate or aluminate.

[0025] In a preferred embodiment of the present invention, in step S4, the specific steps of directional local melting of the green compact are as follows:

[0026] S41, placing the mixed and pressed green compact on a workbench of a laser melting device, and ensuring that the green compact is in a stable position and is easily irradiated by a laser beam;

[0027] S42, setting the laser melting equipment parameters to power 2500w, scanning speed 5mm / s, spot size 0.5mm, melting depth 1mm, and setting a scanning path according to the shape of the compact;

[0028] S43, scanning starts according to the scanning path, and the energy of the laser beam is concentrated on a specific area of ​​the compact, causing the metal powder in the area to melt rapidly and combine with each other;

[0029] S44, after the laser melting is completed, the compact is allowed to cool naturally to room temperature in the equipment;

[0030] In a preferred embodiment of the present invention, the protective gas is argon or nitrogen.

[0031] In a preferred embodiment of the present invention, the total deformation amount of drawing is controlled at 40%, and the total deformation amount of upsetting is also controlled at 40%.

[0032] In a preferred embodiment of the present invention, annealing treatment should be performed after each drawing and upsetting.

[0033] An application in a metal fireplace is a high-purity molybdenum alloy composite material prepared by any of the methods for preparing a high-purity molybdenum alloy composite material.

[0034] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0035] (1) High-purity molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder are selected as raw materials, each powder is modified, the modified powder is placed in a V-type mixer for mixing according to a certain ratio, the mixed alloy powder is placed in a pressing mold, a hydraulic press is used to press to form a green compact, the green compact is directionally partially melted, the green compact after directionally partially melted is placed in a sintering furnace, a protective gas is introduced into the sintering furnace to prevent the alloy powder from being oxidized during the sintering process, so as to ensure that the alloy powder is fully melted and combined, and after the sintering is completed, the green compact is cooled to room temperature with the furnace to obtain a molybdenum alloy blank, and the molybdenum obtained by sintering is subjected to a sintering process. The alloy billet is subjected to multiple drawing and roughening processes to improve its shape and dimensional accuracy. The roughened molybdenum alloy billet is annealed under vacuum conditions and then cooled to room temperature with the furnace to obtain the final material. Compared with the prior art, the material is modified in advance to form a uniform and dense protective film on the alloy surface, so that the melt wets and penetrates between the powder particles more evenly, thereby improving the density and uniformity of the material, changing the polarity and charge properties of the powder surface, thereby regulating its interaction with the subsequent treatment liquid, causing microcracks, deformation or peeling on the surface of the powder particles, and increasing the surface roughness. This rough surface structure is conducive to the mechanical interlocking between the powder particles, thereby improving the overall viscosity of the material and reducing the unevenness of the alloy of a high-purity molybdenum alloy composite material prepared as a whole.

[0036] (2) By modifying high-purity molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder, a uniform and dense protective film can be formed first. At the same time, the melt can more evenly wet and penetrate between the powder particles, thereby improving the density and uniformity of the material, changing the polarity and charge properties of the powder surface, thereby regulating the interaction between the powder and the subsequent treatment liquid, causing microcracks, deformation or peeling on the surface of the powder particles, and increasing the surface roughness. This rough surface structure is conducive to the mechanical interlocking between the powder particles, thereby improving the overall viscosity of the material and reducing the unevenness within the alloy of the high-purity molybdenum alloy composite material prepared as a whole.

[0037] (3) A combination of three modification methods was used during the modification treatment, which can give full play to the advantages of each modification method and form a complementary effect; surface chemical coating can improve the quality and performance of the alloy surface; precipitation reaction can form a uniformly distributed strengthening phase inside the alloy, thereby improving the strength and hardness of the alloy; and mechanochemical modification can make the molecules / atoms inside the alloy more tightly arranged through mechanical action, thereby significantly enhancing the performance of the alloy.

[0038] (4) Directional local melting of the pressed billet is carried out, and the alloy is made to melt and solidify rapidly in a local area, thereby refining the grains, reducing defects, and improving the uniformity and density of the alloy; making the molecular / atomic arrangement inside the alloy more orderly, enhancing the interaction force between atoms, reducing the unevenness within the alloy, and further improving the performance of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0040] Figure 1 is a flow chart of a preferred embodiment of the present invention; DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0043] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the scope of protection of the present application. In addition, the terms "first", "second", etc. are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, features defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the invention, unless otherwise specified, "multiple" means two or more.

[0044] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood by specific circumstances.

[0045] like Figure 1 As shown, a preparation method of a high-purity molybdenum alloy composite material and its application in a metal fireplace include:

[0046] S1. Select high-purity molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder and modify them respectively;

[0047] S2, placing the modified molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder in a V-type mixer according to the weight ratio and mixing them, and adding a dispersant during the mixing process;

[0048] S3, placing the mixed alloy powder into a pressing mold, using a hydraulic press to press, the pressing pressure is 200MPa, the holding time is 5min, to obtain a compact;

[0049] S4, performing directional local melting on the compact;

[0050] S5. Place the compact after partial melting into a sintering furnace and pre-sinter it under vacuum conditions. The vacuum degree is controlled at 10 -3 Pa, heating rate is 5℃ / min, heating to 1600℃, keeping temperature for 2h;

[0051] S6. Formal sintering: Introduce protective gas into the sintering furnace, continue to heat up to 2000℃, and sinter for 8 hours. The temperature and atmosphere should be strictly controlled during the sintering process to ensure that the alloy powder is fully melted and combined. After sintering, cool to room temperature with the furnace to obtain a molybdenum alloy billet.

[0052] S7. The sintered molybdenum alloy billet is subjected to multiple drawing and roughening processes.

[0053] S8, annealing the roughened molybdenum alloy billet under vacuum conditions at a temperature of 1200° C. for 2 hours, and cooling the billet to room temperature to obtain a final material.

[0054] Specifically, the purity of molybdenum powder is 99.95%, the purity of titanium powder is 99%, the purity of zirconium powder is 99%, the purity of tungsten powder is 99%, and the purity of nickel powder is 99%.

[0055] Specifically, the speed of the V-type mixer is set to 20 r / min, and the mixing time is 20 h.

[0056] More specifically, the loading amount is controlled to be about 3 / 5 of the volume of the V-type mixer, so that uniform mixing can be ensured during mixing.

[0057] In step S1, the modification process includes:

[0058] S11, washing the powder with ethanol to remove surface impurities, and placing the washed powder in a drying oven to remove moisture;

[0059] S12, using a combination of three modification methods: surface chemical coating modification method, precipitation reaction modification method and mechanochemical modification method;

[0060] S13, after the modification treatment, the powder is washed to remove unreacted modifier and impurities;

[0061] After washing, the powder is dried in a drying oven to remove moisture;

[0062] Furthermore, in step S12, it specifically includes:

[0063] S121. Place molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder in different containers respectively; add an appropriate amount of silane coupling agent solution (KH-550) to each container to ensure that the solution can completely cover the powder; at 60°C, make the silane coupling agent uniformly adsorbed on the surface of the powder by stirring or ultrasound; after 2-4 hours, take out the powder, wash it with ethanol or other solvents to remove the unreacted silane coupling agent; place the washed powder in an oven to dry to obtain a modified powder;

[0064] S122, uniformly mixing the molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder modified in step S121; adding sodium hydroxide solution to the mixed powder to ensure that the concentration and pH value of the solution are appropriate; stirring at 60° C. to allow sodium hydroxide to react with metal ions on the surface of the powder to generate hydroxide precipitates; after the reaction is completed, filtering and washing the precipitates to remove unreacted sodium hydroxide and impurities; drying the washed precipitates in an oven to obtain modified powders;

[0065] S123, uniformly mixing the molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder modified in step S122; placing the mixed powder in an ultrafine grinding device to activate the particle surface through strong mechanical force; during the grinding process, adding stearic acid to react or adsorb the modifier to the powder surface through mechanical force; after the grinding and modification are completed, taking out the powder, screening and drying it to obtain the final modified powder.

[0066] Specifically, the uniform adsorption of modifiers such as silane coupling agent (KH-550) on the powder surface can improve the wettability between the powder and the subsequent processing liquid (such as the melt during sintering). This helps the melt to more evenly wet and penetrate between the powder particles during the sintering process, thereby improving the density and uniformity of the material. One end of the silane coupling agent can chemically bond with the metal atoms or functional groups on the powder surface, and the other end may have a functional group that can react with the components in the subsequent processing liquid. This chemical bonding not only enhances the activity of the powder surface, but also promotes the close bonding between the powder and the subsequent processing liquid.

[0067] By depositing a layer of inorganic substances (hydroxides) on the powder surface through precipitation reaction, the polarity and charge properties of the powder surface can be changed, thereby regulating its interaction with the subsequent treatment liquid. This regulation improves the wettability of the melt and reduces the porosity.

[0068] More specifically, the modification treatment can also improve the fluidity of the powder, making it easier to form a uniform compact and a dense sintered body during pressing and sintering. The improvement in fluidity helps to reduce the formation of pores and defects, thereby improving the overall performance and viscosity of the material.

[0069] More specifically, during the mechanochemical modification process, strong mechanical forces cause microcracks, deformation or peeling on the surface of the powder particles, increasing the surface roughness. This rough surface structure is conducive to the mechanical interlocking between the powder particles, thereby improving the overall viscosity of the material.

[0070] More specifically, modifiers such as stearic acid can be attached to the powder surface by physical adsorption or chemical adsorption. The interaction forces between these modifier molecules (such as van der Waals forces, hydrogen bonds, etc.) help increase the viscosity between powder particles.

[0071] Furthermore, the weight ratio of the molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder is 65:7:7:8:13.

[0072] Specifically, molybdenum powder has a high melting point, high strength and hardness, and is the main component of the composite material, which provides the basic structural strength; tungsten powder also has a high melting point and high hardness, which can further enhance the hardness and wear resistance of the composite material; although titanium powder and zirconium powder have relatively low hardness, their addition can improve the toughness and corrosion resistance of the material;

[0073] More specifically, the tungsten powder and molybdenum powder have excellent wear resistance, which makes the composite material perform well in friction and wear environments; while the titanium powder and zirconium powder have good corrosion resistance, which can protect the composite material from chemical erosion.

[0074] More specifically, the high melting points of molybdenum powder and tungsten powder enable the composite material to maintain stable performance at high temperatures.

[0075] Furthermore, the dispersant used is a silicate or an aluminate;

[0076] Specifically, these dispersants usually have high stability and heat resistance; because powder particles tend to agglomerate during the mixing process, and dispersants can form a protective film on the surface of the particles to prevent direct contact and agglomeration between the particles;

[0077] More specifically, dispersants can also reduce the surface tension between powder particles and solvent or air, improving the wettability of the powder, thereby facilitating uniform dispersion of the powder in the mixer;

[0078] At the same time, through the action of the dispersant, the powder particles can be more evenly distributed in the mixer, improving the mixing effect and ensuring the smooth progress of subsequent processing.

[0079] In step S4, the specific steps of directional local melting of the green compact are as follows:

[0080] S41, placing the mixed and pressed green compact on a workbench of a laser melting device, and ensuring that the green compact is in a stable position and is easily irradiated by a laser beam;

[0081] S42, setting the laser melting equipment parameters to power 2500w, scanning speed 5mm / s, spot size 0.5mm, melting depth 1mm, and setting a scanning path according to the shape of the compact;

[0082] S43, scanning starts according to the scanning path, and the energy of the laser beam is concentrated on a specific area of ​​the compact, causing the metal powder in the area to melt rapidly and combine with each other;

[0083] S44, after the laser melting is completed, the compact is allowed to cool naturally to room temperature in the equipment;

[0084] Specifically, through directional local melting, the microstructure of the green compact can be improved, the initial bonding between metal powders can be promoted, and a better foundation can be provided for the subsequent formal sintering. At the same time, directional local melting can also help eliminate defects and stresses inside the green compact, and improve the performance and quality of the final product.

[0085] Furthermore, in step S6, the protective gas is argon or nitrogen; they can effectively isolate the air and provide a pure environment for the sintering process.

[0086] It should be noted that in step S6, the temperature and atmosphere in the sintering furnace need to be strictly controlled throughout the sintering process. Temperature fluctuations may affect the rate of the sintering reaction and the degree of modification, thereby affecting the quality and performance of the sintered body. The control of the atmosphere is related to whether the sintered body will be contaminated by impurities, thereby affecting its purity and performance.

[0087] Furthermore, the total deformation of drawing is controlled at 40%, and the total deformation of upsetting is also controlled at 40%.

[0088] Specifically, during the drawing process, the material will undergo plastic deformation, and the amount of deformation directly affects the mechanical properties and microstructure of the material; controlling the total deformation within 40% can ensure that the material will not produce cracks, fractures or severe work hardening due to excessive stretching during the deformation process, thereby maintaining the good performance of the material.

[0089] At the same time, moderate drawing deformation can promote the refinement and recrystallization of the internal grains of the material, which helps to improve the material's microstructure and improve the material's toughness, strength and other mechanical properties. However, if the deformation is too large, it may lead to excessive grain refinement, forming an unstable microstructure, which in turn reduces the material's performance.

[0090] More specifically, during the upsetting process, the material is compressed and deformed, and the amount of deformation directly affects the density and uniformity of the material. Controlling the total deformation within 40% can ensure that the material forms a good dense structure and uniform microstructure during the upsetting process, thereby improving the overall performance of the material.

[0091] If the deformation of the upsetting is too large, it may cause serious plastic deformation and residual stress inside the material, and even cause cracking and damage to the material. Controlling the total deformation within 40% can avoid these adverse factors and ensure the stability and reliability of the material.

[0092] It should be noted that in step S8, appropriate annealing treatment should be carried out after each drawing and upsetting, because during the upsetting process, the material will undergo large plastic deformation, thereby generating internal stress. Annealing treatment can effectively eliminate these stresses and improve the stability and service life of the material.

[0093] At the same time, annealing treatment can reduce the brittleness of the material, improve its toughness and plasticity, and make it easier for subsequent processing and use.

[0094] And cooling with the furnace can avoid cracks and deformation of the material during rapid cooling, ensuring the integrity and stability of the material.

[0095] An application in a metal fireplace is a high-purity molybdenum alloy composite material prepared by any of the methods for preparing a high-purity molybdenum alloy composite material.

[0096] Example 1

[0097] S1. Select high-purity molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder and modify them respectively;

[0098] S11, washing the powder with ethanol to remove surface impurities, and placing the washed powder in a drying oven to remove moisture;

[0099] S12, using a combination of three modification methods: surface chemical coating modification method, precipitation reaction modification method and mechanochemical modification method;

[0100] S121. Place molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder in different containers respectively; add an appropriate amount of silane coupling agent solution (KH-550) to each container to ensure that the solution can completely cover the powder; at 60°C, make the silane coupling agent uniformly adsorbed on the surface of the powder by stirring or ultrasound; after 2-4 hours, take out the powder, wash it with ethanol or other solvents to remove the unreacted silane coupling agent; place the washed powder in an oven to dry to obtain a modified powder;

[0101] S122, uniformly mixing the molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder modified in step S121; adding sodium hydroxide solution to the mixed powder to ensure that the concentration and pH value of the solution are appropriate; stirring at 60° C. to allow sodium hydroxide to react with metal ions on the surface of the powder to generate hydroxide precipitates; after the reaction is completed, filtering and washing the precipitates to remove unreacted sodium hydroxide and impurities; drying the washed precipitates in an oven to obtain modified powders;

[0102] S123, uniformly mixing the molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder modified in step S122; placing the mixed powder in an ultrafine grinding device to activate the particle surface through strong mechanical force; during the grinding process, adding stearic acid to react or adsorb the modifier to the powder surface through mechanical force; after the grinding and modification are completed, taking out the powder, screening and drying it to obtain the final modified powder.

[0103] S13, after the modification treatment, the powder is washed to remove unreacted modifier and impurities;

[0104] After washing, the powder is dried in a drying oven to remove moisture;

[0105] S2, mixing the modified molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder in a weight ratio of 65:7:7:8:13 in a V-type mixer, and adding silicate during the mixing process;

[0106] S3, placing the mixed alloy powder into a pressing mold, using a hydraulic press to press, the pressing pressure is 200MPa, the holding time is 5min, to obtain a compact;

[0107] S4, performing directional local melting on the compact;

[0108] S41, placing the mixed and pressed green compact on a workbench of a laser melting device, and ensuring that the green compact is in a stable position and is easily irradiated by a laser beam;

[0109] S42, setting the laser melting equipment parameters to power 2500w, scanning speed 5mm / s, spot size 0.5mm, melting depth 1mm, and setting a scanning path according to the shape of the compact;

[0110] S43, scanning starts according to the scanning path, and the energy of the laser beam is concentrated on a specific area of ​​the compact, causing the metal powder in the area to melt rapidly and combine with each other;

[0111] S44, after the laser melting is completed, the compact is allowed to cool naturally to room temperature in the equipment;

[0112] S5, placing the compact after directional local melting into a sintering furnace, and pre-sintering under vacuum conditions, with the vacuum degree controlled below Pa, heating at a rate of 5°C / min, heating to 1600°C, and keeping the temperature for 2h;

[0113] S6. Formal sintering: Introduce argon into the sintering furnace, continue to heat up to 2000℃, and sinter for 8 hours. The temperature and atmosphere should be strictly controlled during the sintering process to ensure that the alloy powder is fully melted and combined. After sintering, cool to room temperature with the furnace to obtain a molybdenum alloy billet.

[0114] S7, the molybdenum alloy blank obtained by sintering is subjected to multiple drawing and roughening treatments; the total deformation of the drawing is controlled at 40%, and the total deformation of the roughening is also controlled at 40%

[0115] S8, annealing the roughened molybdenum alloy billet under vacuum conditions at a temperature of 1200° C. for 2 hours, and cooling the billet to room temperature to obtain a final material.

[0116] Comparative Example 1

[0117] Based on Example 1, the difference is that high-purity molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder are selected without modification;

[0118] Comparative Example 2

[0119] Based on Example 1, the difference is that: in step S12, only the surface chemical coating modification method is used;

[0120] Place molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder in different containers respectively; add an appropriate amount of silane coupling agent solution (KH-550) to each container to ensure that the solution can completely cover the powder; at 60°C, make the silane coupling agent uniformly adsorbed on the surface of the powder by stirring or ultrasound; after 2-4 hours, take out the powder and wash it with ethanol or other solvents to remove the unreacted silane coupling agent; place the washed powder in an oven to dry to obtain a modified powder;

[0121] Comparative Example 3

[0122] Based on Example 1, the difference is that: in step S12, only the precipitation reaction modification method and the mechanochemical modification method are used;

[0123] Molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder are mixed uniformly; sodium hydroxide solution is added to the mixed powder to ensure that the concentration and pH value of the solution are appropriate; sodium hydroxide is reacted with metal ions on the surface of the powder by stirring at 60°C to generate hydroxide precipitation; after the reaction is completed, the precipitate is filtered and washed to remove unreacted sodium hydroxide and impurities; the washed precipitate is placed in an oven to dry to obtain a modified powder;

[0124] Comparative Example 4

[0125] Based on Example 1, the difference is that: in step S12, only the mechanochemical modification method is used;

[0126] Molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder are mixed evenly; the mixed powder is placed in an ultrafine grinding device to activate the particle surface through strong mechanical force; during the grinding process, stearic acid is added to react or adsorb the modifier to the powder surface through mechanical force; after the grinding and modification are completed, the powder is taken out, sieved and dried to obtain the final modified powder.

[0127] Comparative Example 5

[0128] Based on Example 1, the difference is that: the green compact is not subjected to directional local melting;

[0129] Experimental Example 1

[0130] The verification is carried out through four experimental categories; namely, alloy composition analysis, mechanical properties test, thermal properties test and microstructure observation, specifically:

[0131] Alloy composition analysis: Alloy samples were taken from Example 1 and Comparative Examples 1-5 to ensure that the samples were representative and free of contamination; the alloy samples were ground into powder to meet the test requirements of the X-ray fluorescence spectrometer; the samples were tested using the X-ray fluorescence spectrometer to record the content and distribution data of each element

[0132] Mechanical properties test: According to the national standard GB / T 228.1-2010, samples were taken from Example 1 and Comparative Examples 1-5 for tensile tests. The tensile strength, yield strength, hardness and other mechanical properties of the alloy were tested through tensile tests and hardness tests.

[0133] Thermal performance test: The alloy samples in Example 1 and Comparative Examples 1-5 were tested using a thermal conductivity tester and an optical interferometer; the thermal conductivity tester was turned on, the measurement parameters were set to a steady-state method, the ambient temperature was 25° C., the heating power was 10 W, the sample was placed on the heating plate of the tester, ensuring that the sample was in close contact with the heating plate, the measurement program was started, and the thermal conductivity was recorded;

[0134] Turn on the optical interferometer, set the measurement parameters from room temperature to 200°C, and the heating rate to 5°C / min; at room temperature (25°C), use the optical interferometer to record the initial length L0 of the sample as 50.000mm; place the sample in a heating furnace, slowly heat it to 200°C, and keep it at this temperature for 30 minutes; use the optical interferometer to record the length L1 of the sample at 200°C as 50.025mm; calculate the thermal expansion coefficient based on the measurement results and temperature changes.

[0135] Microstructure observation: The alloy sample was cut into thin slices (less than 100 nm thick) and subjected to ion thinning or chemical thinning treatment to prepare transmission samples.

[0136] Turn on the TEM instrument, place the sample on the TEM sample stage, start the observation program, adjust the magnification and focal length, and observe the microstructure morphology and crystal structure.

[0137] The data in Table 1 are obtained through the above four experiments:

[0138] Table 1:

[0139]

[0140]

[0141] According to the data in Table 1, it can be seen that, according to the alloy uniformity obtained by microstructure observation and composition analysis, and the tensile strength, yield strength and hardness data obtained by mechanical property test, the data of Example 1 is the best, and the data of Comparative Example 1 is poor. The reason is that: compared with Comparative Example 1, Example 1 can form a uniform and dense protective film on the alloy surface through surface chemical coating, and this protective film can prevent the erosion of the external environment, and at the same time enhance the hardness and wear resistance of the alloy surface, make the molecular / atomic arrangement on the alloy surface more regular, and enhance the interaction force between atoms, thereby improving the overall performance of the alloy;

[0142] According to the alloy uniformity obtained by microstructure observation and composition analysis, and the tensile strength, yield strength and hardness data obtained by mechanical property test, Example 1 has the best data compared with Comparative Examples 2, 3 and 4, while Comparative Examples 2, 3 and 4 are relatively poor. The reason is that: the combination of the three modification methods can give full play to the advantages of each modification method and form a complementary effect; the surface chemical coating can improve the quality and performance of the alloy surface; the precipitation reaction can form a uniformly distributed strengthening phase inside the alloy, thereby improving the strength and hardness of the alloy; the mechanochemical modification can make the molecules / atoms inside the alloy more closely arranged through mechanical action, thereby significantly enhancing the performance of the alloy;

[0143] According to the alloy uniformity obtained by microstructure observation and composition analysis, and the tensile strength, yield strength and hardness data obtained by mechanical property testing, Example 1 has the best data compared with Comparative Example 5, while Comparative Example 5 is worse. The reason is that: by making the alloy melt and solidify rapidly in a local area, the grains are refined, defects are reduced, and the uniformity and density of the alloy are improved; the molecular / atomic arrangement inside the alloy is made more orderly, the interaction force between atoms is enhanced, and the performance of the alloy is further improved.

[0144] According to the data in Table 1, the data of thermal conductivity and thermal expansion coefficient obtained by thermal performance test are evaluated. The data of Example 1 is the best, and the data of Comparative Example 1 is poor. The reason is that: Example 1 forms a more uniform and dense protective layer on the alloy surface through surface chemical coating and other modification methods, reducing micro defects and pollutants; this protective layer can transfer heat more effectively because the heat transfer between molecules is smoother, reducing scattering and reflection; the modification may also improve the microstructure of the alloy surface, making the heat conduction path more optimized; the microstructure of the alloy surface in Example 1 is more uniform, reducing stress concentration points. When the temperature changes, the alloy can expand and contract more evenly, thereby reducing the thermal expansion coefficient;

[0145] According to the thermal conductivity and thermal expansion coefficient data obtained by the thermal performance test, compared with comparative examples 2, 3, and 4, the data of Example 1 is the best, while comparative examples 2, 3, and 4 are relatively poor. The reason is that: Example 1 can more comprehensively optimize the microstructure and performance of the alloy by combining the three methods of surface chemical coating, precipitation reaction, and mechanochemical modification. This combined modification method can reduce defects and impurities inside the alloy, improve the uniformity and density of the alloy, and thus transfer heat more effectively; by changing the lattice structure and chemical bond type inside the alloy, the thermal conductivity is further improved; in terms of thermal expansion coefficient, Example 1 can more comprehensively optimize the microstructure and performance of the alloy by combining the modification method, reduce stress concentration points and micro defects; this allows the alloy to expand and contract more evenly when the temperature changes.

[0146] According to the thermal conductivity and thermal expansion coefficient data obtained by thermal performance testing, Example 1 has the best data compared to Comparative Example 5, while Comparative Example 5 is relatively poor. The reason is that: in Example 1, the microstructure of the alloy is significantly refined, the grain size is reduced, and the phase distribution is more uniform through directional local melting. This change in the microstructure allows heat to pass more smoothly through the interior of the alloy during conduction, thereby improving thermal conductivity. In addition, directional local melting may further improve thermal conductivity by changing the lattice orientation and chemical bond type inside the alloy; at the same time, directional local melting makes the microstructure of the alloy more uniform and delicate, reducing stress concentration and microscopic defects. This allows the alloy to expand and contract more evenly when the temperature changes, thereby reducing the thermal expansion coefficient.

[0147] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a high-purity molybdenum alloy composite material, characterized in that: include: S1. Select high-purity molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder and modify them respectively; S2, placing the modified molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder in a V-type mixer according to the weight ratio and mixing them, and adding a dispersant during the mixing process; S3, placing the mixed alloy powder into a pressing mold, using a hydraulic press to press, the pressing pressure is 200MPa, the holding time is 5min, to obtain a compact; S4, performing directional local melting on the compact; S5. Place the compact after partial melting into a sintering furnace and pre-sinter it under vacuum conditions. The vacuum degree is controlled at 10 -3 Pa, heating rate is 5℃ / min, heating to 1600℃, keeping temperature for 2h; S6. Formal sintering: Introduce protective gas into the sintering furnace, continue to raise the temperature to 2000℃, and sinter for 8 hours. During the sintering process, the temperature and atmosphere should be strictly controlled to ensure that the alloy powder is fully melted and combined. After the sintering is completed, cool it to room temperature with the furnace to obtain a molybdenum alloy billet. S7, performing multiple drawing and roughening treatments on the molybdenum alloy blank obtained by sintering; S8. Annealing the roughened molybdenum alloy billet under vacuum conditions at an annealing temperature of 1200° C. for 2 h; cooling to room temperature with the furnace after annealing to obtain the final material.

2. The method for preparing a high-purity molybdenum alloy composite material according to claim 1, characterized in that: In step S1, the specific steps of the modification treatment are: S11, washing the powder with ethanol to remove surface impurities, and placing the washed powder in a drying oven to remove moisture; S12, using a combination of three modification methods: surface chemical coating modification method, precipitation reaction modification method and mechanochemical modification method; S13, after the modification treatment, the powder is washed to remove unreacted modifier and impurities; After washing, the powder is dried in a drying oven to remove moisture.

3. The method for preparing a high-purity molybdenum alloy composite material according to claim 2, characterized in that: In step S12, it specifically includes: S121. Place molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder in different containers respectively; add an appropriate amount of silane coupling agent solution (KH-550) to each container to ensure that the solution can completely cover the powder; at 60°C, make the silane coupling agent uniformly adsorbed on the surface of the powder by stirring or ultrasound; after 2-4 hours, take out the powder, wash it with ethanol or other solvents to remove the unreacted silane coupling agent; place the washed powder in an oven to dry to obtain a modified powder; S122, uniformly mixing the molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder modified in step S121; adding sodium hydroxide solution to the mixed powder to ensure that the concentration and pH value of the solution are appropriate; stirring at 60° C. to allow sodium hydroxide to react with metal ions on the surface of the powder to generate hydroxide precipitates; after the reaction is completed, filtering and washing the precipitates to remove unreacted sodium hydroxide and impurities; drying the washed precipitates in an oven to obtain modified powders; S123, uniformly mixing the molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder modified in step S122; placing the mixed powder in an ultrafine grinding device to activate the particle surface through strong mechanical force; during the grinding process, adding stearic acid to react or adsorb the modifier to the powder surface through mechanical force; after the grinding and modification are completed, taking out the powder, screening and drying it to obtain the final modified powder.

4. The method for preparing a high-purity molybdenum alloy composite material according to claim 1, characterized in that: The weight ratio of the molybdenum powder, titanium powder, zirconium powder, tungsten powder and nickel powder is 65:7:7:8:

13.

5. The method for preparing a high-purity molybdenum alloy composite material according to claim 1, characterized in that: The dispersant used is silicate or aluminate.

6. The method for preparing a high-purity molybdenum alloy composite material according to claim 1, characterized in that: In step S4, the specific steps of directional local melting of the green compact are as follows: S41, placing the mixed and pressed green compact on a workbench of a laser melting device, and ensuring that the green compact is in a stable position and is easily irradiated by a laser beam; S42, setting the laser melting equipment parameters to power 2500w, scanning speed 5mm / s, spot size 0.5mm, melting depth 1mm, and setting a scanning path according to the shape of the compact; S43, scanning starts according to the scanning path, and the energy of the laser beam is concentrated on a specific area of ​​the compact, causing the metal powder in the area to melt rapidly and combine with each other; S44. After laser melting is completed, the compact is allowed to cool naturally to room temperature in the equipment.

7. The method for preparing a high-purity molybdenum alloy composite material according to claim 1, characterized in that: The shielding gas is argon or nitrogen.

8. The method for preparing a high-purity molybdenum alloy composite material according to claim 1, characterized in that: The total deformation of drawing is controlled at 40%, and the total deformation of roughening is also controlled at 40%.

9. The method for preparing a high-purity molybdenum alloy composite material according to claim 1, characterized in that: Annealing should be carried out after each drawing and roughening.

10. Application in a metal fireplace, characterized in that: A high-purity molybdenum alloy composite material prepared by the method for preparing a high-purity molybdenum alloy composite material according to any one of claims 1 to 9.